Middle helladic and early Mycenaean mortuary customs in the southern and western Peloponnese - Boyd, Michael John (University of Edinburgh, 1999)
The aim of this thesis is to set out the evidence for burial practices In the southern and western Peloponnese of Greece during the middle helladic and early Mycenaean periods (circa 2050/2000 B.C. to 1445/1415 B.C.), and to interprett he evidence in terms of human action. The first half of the thesis sets out the scope of the research. Chapter One Is a basic introduction to the material, including the chronological boundaries, a basic description of the material, problems of dating sites, the topography of the region, and a summary of survey results in the area. In Chapter Two some approaches to mortuary data are examined, in particular notions that architecture can be classified in a meaningful way in relation to the past and that funerary ceremonies in some way reflect the lifetime status of the recently dead, as well as Ideas about the relationships between mortuary architecture, funerary practices and society. It is suggested that burial practices are often seen to be bound up in the reproduction of pan-helladic social structures in the form of the 'Mycenaean civilisation', and it is suggested that in the early Mycenaean period burial practices are seen to constitute one of only two principal signifiers of that civilisation (the other being Mycenaean pottery) Chapter Three sets forth an outline theory of human action with special reference to the mortuary arena. Action is examined through its medium, the human body, and in its setting, the locale. The idea of locale is developed in order to understand how people perceive their environment and interpret space through routine occupancy and movement, and through the propagation of knowledge. Aspects of locale impacting on human action include its place in the landscape architecture, material culture and tradition. The human body as medium of action is considered in how it may interact with its environment and with others. Chapter Four includes a review of the epistemological approaches of paste excavators to their material, and the effect of this on the nature and content of published reports. The second part of this chapter examines the question of how to investigate human action In the mortuary locale on the basis of the available evidence. An analytical methodology is presented that allows for examination of the evidence in terms of four main areas of human activity: grave location, grave construction, pre-mortuary rites, and rites in the tomb. The second half of the thesis presents an analysis of the evidence in order to answer the following generic questions: where were tombs situated, how were they occupied and what was their place In the encultured landscape; what was the meaning and effect of architecture; what did people do In tombs and as part of mortuary rites; how were practices and structures maintained and altered through time, and what brought about their widespread reproduction? The evidence on which the analysis Is based Is presented In Appendix One, which contains detailed descriptions and illustrations of 61 sites In the study area. The place of the grave In the landscape Is examined in Chapter Five; mortuary architecture Is analysed In Chapter Six; evidence for preparatory acts before funerals Is reviewed in Chapter Seven; and mortuary practices are considered In Chapter Eight. Chapter Nine presents the general conclusions of the study, Including both a summary of burial practices as evidenced, and a historical framework within which those practices may be set. Areas of continuity and change In tradition are Identified and explained. The chapter considers the Implications of these conclusions on the use of burial practices in the study of 'Mycenaean civilization', confirming that variations In time and space suggest closer study of local and regional archaeologies should be a priority In future research aims.
Keywords: Archaeology; Helladic; Mycenaean